Organic salt induced electrospinning gradient effect: Achievement of BiVO4 nanotubes with promoted photocatalytic performance - Lv, Chade; Sun, Jingxue; Chen, Gang; Zhou, Yansong; Li, Danying; Wang, Zukun; Zhao, Boran (Applied catalysis. B, Environmental, 2017)
Organic salt induced electrospinning gradient effect can achieve tubular nanostructure without template. [Display omitted] •Organic salt induced gradient effect is proposed for fabricating tubular structure.•First report on electrospun mesoporous BiVO4 nanotube with enhanced light harvesting.•The proposed electrospinning mechanism possess excellent applicability.•Tubular BiVO4 exhibits improved photocatalytic performance for reduction of Cr(VI). Tubular nanostructure becomes the researchful focus in environmental purification because of its unique features, however, the hollow fibrous BiVO4, famous as an efficient photocatalyst for water purification and oxidation, has not been achieved yet. Here, we employ organic vanadium salt to fabricate BiVO4 nanotubes by single-spinneret electrospinning without template. The organic salt can induce electrospinning gradient effect which plays a key role in the achievement of tubular nanostructure. Benefit from the unique structural properties of tubular nanostructure, BiVO4 nanotubes possess hollow interior, leading to strong light harvesting ability and large surface areas. For photocatalytic reduction of Cr(VI), these contributions from tubular nanostructure could promote the photocatalytic performance relative to solid BiVO4 nanofibers. This organic salt induced electrospinning gradient effect is not subject to the usage amount, ratio and kind of as-employed salt, endowing the electrospinning method with bright vista for the fabrication of other materials with tubular nanostructure.